ANALISIS PERBANDINGAN KINERJA KEUANGAN DENGAN METODE ECONOMIC VALUE ADDED DAN MARKET VALUE ADDED PADA PT INDOSAT .TBK DAN PT XL AXIATA TBK ( PERIODE TAHUN 2016-2021) - Mujiyani Mujiyani; Avira Putri Salma (Jurnal Ilmiah Multidisiplin, 2022)
In the midst of intense competition between operators, every company is required to improve the quality of service and products they have. Companies are also required to focus on important aspects related to the performance of a company. This study aims to determine the comparison of financial performance between PT Indosat Tbk and PT XL Axiata in the 2016-2021 period using the Economic Value Added (EVA) and Market Value Added (MVA) methods. This research is quantitative research that originates from secondary data, namely the annual financial reports of PT Indosat Tbk and PT XL Axiata Tbk in the form of statements of financial position and statements of income for the companies for the 2016-2021 period. The results of the analysis as a whole show fluctuating values. The value generated by the EVA method shows that 1 (one) company produces a positive value or > 0, while 1 (one) company produces a negative value or < 0. The results of calculating the MVA value show that both companies are able to produce an MVA value > 0. This shows that the company succeeded in increasing the value of capital invested by shareholders.